2006
DOI: 10.1093/annonc/mdj130
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of oral vinorelbine for the treatment of metastatic breast cancer in patients ≥65 years of age: an NCCTG study

Abstract: Oral vinorelbine as a single agent at these dose and schedule in this population of women > or = 65 years is well tolerated but has a low level of objective efficacy for the treatment of metastatic breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…[28][29][30] A phase I study of oral vinorelbine and capecitabine has established a recommended dose of vinorelbine 60 mg/m 2 per week and capecitabine 2000 mg/m 2 days 1-14 every 3 weeks 31 and recently a phase II study of the oral combination in pretreated MBC has shown a response rate of 39%. 32 Although it Leucopenia 25 19 3 1 Neutropenia 16 19 15 1 Anemia 13 2 0 0 Thrombocytopenia 2 0 0 0 Non hematological Nausea 12 4 1 0 Emesis 6 3 0 0 Diarrhea 16 2 2 0 Dehydration 1 0 1 0 Stomatitis 12 0 1 0 Hand-foot syndrome 8 2 0 0 Neuropathy 7 0 1 0 Fatigue 19 12 2 0 Other 34 12 2 0 NCI CTC, National Cancer Institute Common Toxicity Criteria.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] A phase I study of oral vinorelbine and capecitabine has established a recommended dose of vinorelbine 60 mg/m 2 per week and capecitabine 2000 mg/m 2 days 1-14 every 3 weeks 31 and recently a phase II study of the oral combination in pretreated MBC has shown a response rate of 39%. 32 Although it Leucopenia 25 19 3 1 Neutropenia 16 19 15 1 Anemia 13 2 0 0 Thrombocytopenia 2 0 0 0 Non hematological Nausea 12 4 1 0 Emesis 6 3 0 0 Diarrhea 16 2 2 0 Dehydration 1 0 1 0 Stomatitis 12 0 1 0 Hand-foot syndrome 8 2 0 0 Neuropathy 7 0 1 0 Fatigue 19 12 2 0 Other 34 12 2 0 NCI CTC, National Cancer Institute Common Toxicity Criteria.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment was fairly well tolerated with G3 neutropoenia in 12.5%, fatigue in 12.5% of the patients, and G2 neuromotor and neurosensory toxicities in 12.5 and 8.3%, respectively. Overall, the activity of this drug in first-or second-line therapies in the elderly population is low [50].…”
Section: Oral VI In the Elderlymentioning
confidence: 99%
“…5 Many studies have put effort into maintaining the vinorelbine concentration surrounding tumor cells in order to improve the anticancer activity of vinorelbine. 6,7 Liposomal encapsulation is practical for vinorelbine to extend its circulation time and to increase its accumulation in tumor tissue.…”
Section: Introductionmentioning
confidence: 99%